2011
DOI: 10.1177/039463201102400415
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Content in Daily Food Portions and the Influence of Supplementation

Abstract: Magnesium is one of the most important cations for an organism. The aim of our study is to evaluate whether the use of a magnesium formulation as a diet supplement or medical treatment is necessary. The 24-hour recall method was used to obtain information regarding the daily magnesium consumption of 949 people. The results were compared with the Estimated Average Requirement (EAR) and Recommended Daily Allowance (RDA) values. The average daily requirement for magnesium was exceeded by 292 (183 women and 109 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, Niedworok et al report-ed that in a group of 949 people they found that the recommended daily dose for magnesium was exceeded by 292 mg/day (183 women and 109 men). The authors emphasized that an uncontrolled excessive magnesium intake by both men and women may constitute a health threat [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, Niedworok et al report-ed that in a group of 949 people they found that the recommended daily dose for magnesium was exceeded by 292 mg/day (183 women and 109 men). The authors emphasized that an uncontrolled excessive magnesium intake by both men and women may constitute a health threat [9].…”
Section: Introductionmentioning
confidence: 99%